The role of artificial intelligence in cardio-oncology: present and future: A review - Yuri I. Buziashvili; Elmira U. Asymbekova; Elvina F. Tugeeva; Firdavsdzhon R. Akildzhonov (ZAO "Consilium Medicum", 2023)
Cardiooncology has been developed as a relatively new branch of medicine that focuses on the prevention and treatment of adverse cardiovascular events associated with cancer therapy. Newer, more efficient data acquisition methods, such as the use of artificial intelligence, are desirable to help assess CVR in cancer patients. By extracting hidden patterns and evidence from large volumes of medical data, artificial intelligence can create new predictors and parameters to predict risks in patients with cardio-oncological diseases.